Feasibility of a large prospective study in general practice: an Italian experience. Gruppo di Studio sulla Pressione Arteriosa nell'Anziano. Issue 6565 (17th January 1987) - Avanzini, F; Alli, C; Bettelli, G; Colombo, F; Conforti, L; Pirone, F; Spagnoli, A; Taioli, E; Tognoni, G; Villella, M
Abstract : A study of blood pressure control in elderly outpatients was carried out with the participation of 444 Italian general practitioners. Of 4096 patients aged 65 years or over who were considered for recruitment, 3959 (96.7%) fulfilled all the criteria of admission and were followed up for 12 months. The findings regarding one of the aims of the study--that is, to assess the feasibility of a large scale trial in general practice--are reported. Most (87%) of the doctors completed the study. Their adherence to the protocol was highly satisfactory, leading to an acceptable quality of work. Patients' compliance was also good; 98.6% (3898) of the patients who had fulfilled the admission criteria agreed to participate in the study, and only 4% (158) dropped out. Both of these observations support the feasibility of carrying out prospective studies in general practice. The creation of networks of general practitioners who are prepared to carry out research in their practices would allow treatment and preventive measures to be studied simply and at low cost in the appropriate setting.